2022
DOI: 10.30867/action.v7i1.579
|View full text |Cite
|
Sign up to set email alerts
|

Asupan makanan dengan kejadian stunting pada keluarga nelayan di Kota Bengkulu

Abstract: The prevalence of stunting in coastal areas in fishing families in Bengkulu city is 29,4%. The potential possessed by coastal areas is not accompanied by the welfare of the lives of the people who occupy low economic strata, including in fulfilling nutrition. This study aimed to determine the relationship between energy consumption, protein, fat, carbohydrates, zinc, and iron with the incidence of stunting aged 1-59 months in fishing families in Bengkulu city. The cross-sectional research method was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
2
1
8
Order By: Relevance
“…Bueno's study (2008) also found that consumption of foods that are low in calcium at a growing age will impact growth, especially in the future or adulthood (39). Research in Bengkulu that was conducted by Yuli et al (40) also found that there was a relationship between intake of energy, protein, fat, carbohydrates, and zinc in the incidence of stunting under five (40).…”
Section: Discussionmentioning
confidence: 97%
“…Bueno's study (2008) also found that consumption of foods that are low in calcium at a growing age will impact growth, especially in the future or adulthood (39). Research in Bengkulu that was conducted by Yuli et al (40) also found that there was a relationship between intake of energy, protein, fat, carbohydrates, and zinc in the incidence of stunting under five (40).…”
Section: Discussionmentioning
confidence: 97%
“…Studi Avionita L. dkk tahun 2022 menunjukkan bahwa ada perbedana bermakna asupan energi dengan stunting anak balita 17 . Hasil penelitian Emy Y. dkk tahun 2022 juga melaporkana bahwa ada kaitan bermakna antara asupan energi dengan stunting balita 18 . Namun demikian hasil penelitian Kusdanilah dkk tahun 2021 menyatakan bahwa tidak ada kaitan antara asupan zat gizi makro dengan stunting anak 19 Tubuh membutuhkan protein untuk tumbuh serta untuk mensintesis hormon pertumbuhan, makin banyak hormon yang dihasilkan maka pertumbuhan akan lebih baik 20 Kuantitas dan kualitas dari [21][22][23] .…”
Section: Pembahasanunclassified
“…Hasil studi Avionita L. dkk tahun 2022 menunjukkan bahwa ada perbedana bermakna asupan energi dengan stunting anak balita 17 . Emy Y, dkk tahun 2022 juga melaporkana bahwa ada kaitan bermakna antara asupan energi dengan stunting balita 18 . Namun demikian hasil penelitian Kusdanilah dkk tahun 2021 menyatakan bahwa tidak ada kaitan antara asupan zat gizi makro dengan stunting anak 18 .…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Asupan nutrisi menjadi faktor langsung penyebab kejadian stunting. Asupan nutrisi digunakan dalam bentuk energi dan zat gizi lain yang berfungsi dalam menunjang semua aktivitas tubuh (Yuliantini et al, 2022). Kurangnya asupan energi dan protein menyebabkan tubuh mengalami defisiensi zat gizi, sehingga untuk mengatasi defisit yang dialami, maka simpanan energi dan protein yang digunakan oleh tubuh.…”
Section: Berdasarkan Data World Health Organization (Who) Dalam Kemen...unclassified